Schooling Muslims in Natal : Identity, State and the Orient Islamic Educational Institute. - Vahed, Goolam (University of KwaZulu-Natal Press, 2015)
Traces the labors and fortunes of a set of progressive idealists who, mobilizing merchant capital, transoceanic networks and informal political influence, established the Orient Islamic Educational Institute in 1943 to found schools and promote a secular curriculum that could be integrated with Islamic teaching. Through the story of their Durban flagship project - the Orient Islamic School - the book provides a fascinating account of the changing politics of religious identity, education and citizenship in South Africa.